EFEKTIFITAS PENGAJIAN RUTIN DALAM PENINGKATAN PEMAHAMAN AGAMA ISLAM PADA JAMA’AH IBU-IBU DI DESA BULUREJO KECAMATAN DIWEK KABUPATEN JOMBANG - Khusnul Lathiifah; Imam Syafi’i (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2026)
Understanding Islam in the modern era is fraught with challenges; the tide of globalization and easy access to communication have caused people to forget the true purpose of their lives in this world. This is also true for women, who have become estranged from religious values. Therefore, religious activities are needed to effectively enhance understanding of Islam. One effort to deepen and enhance understanding of Islam is the holding of regular Thursday evening religious study sessions at the Jami’ Mosque in Bulurejo Village, Diwek Subdistrict, Jombang Regency. The purpose of this study is to analyze and describe the implementation of regular religious study sessions in enhancing the understanding of Islam among the congregation in Bulurejo Village, Diwek Subdistrict, Jombang Regency, and to analyze and describe the effectiveness of these regular religious study sessions in improving the understanding of Islam among the women’s congregation held in Bulurejo Village, Diwek Subdistrict, Jombang Regency. To address these issues, this study employed a descriptive qualitative approach for data collection. The data collection methods used in this study were observation, interviews, and documentation. The research process included data collection, data reduction, data presentation, verification, and conclusion. The results of the study indicate that regular religious study sessions are held every Thursday afternoon, led by several instructors and attended by women from Bulurejo and the surrounding areas. Meanwhile, the effectiveness of these sessions is evidenced by a significant improvement in the participants’ understanding of Islam.